(untitled) - Skidmore - Roth, Linda (Missouri, 2005)
Mosby's Drug Guide for Nurses, 6th edition is a portable, current drug handbook containing information on more than 60 drug classifications and 4,000 individual generic and trade name drugs. Developed to meet student needs, this handbook includes detailed coverage of IV drugs; extensive coverage of interactions between drugs, drug classes, herbs, foods, and lab tests; a full-color drug identification guide; and a drug classification section covering groups of drugs by function. A disorders index helps the student locate information about drugs commonly used to treat more than 70 disorders. Special features promote safe medication administration and prevention of drug errors, including identification of high alert drugs, Do-Not-Crush and Nursing Alert icons, special Do-Not-Confuse headings, and guidelines for overdose treatment. Combination drugs are covered in an extensive appendix listing alphabetical brand names along with the products' generic components and dosages.
Keywords: Drug for Nurses,Thuốc dành cho y tá